Hungary in the Egyptian press (1922-1936) - Mohamed, Abdallah Abdel-Ati Abdel-Salam (Études sur la Région Méditerranéenne, 2016)
My essay focuses on the published articles in Egypt concerning the Hungarian situation between 1922-1936. The aim of the paper is to give an abbreviated review of the political, economic, commercial, and military situation of Hungary, and to show the development of the independent "Hungarian kingdom without a king". In this regard, I studied the most important contemporary Egyptian newspapers including the Al-Ahram Arabic daily newspaper, the weekly magazine Al-Musawwir, in addition to the two main English-language newspapers: Egyptian Gazette and Egyptian Mail. I present the image of Hungary and Hungarians in the contemporary Egyptian press. It is worth analyzing how the Egyptian editors, journalists and reporters portrayed the era of the Hungary for the Egyptian public. The articles concerning Hungary and Hungarians and news reports indicate that the Egyptian public was well-informed about the developments of Hungary after the collapse of the Austro-Hungarian Monarchy in certain periods. The Egyptian press portrayed Miklós Horthy, the Hungarian regent as a positive figure, and felt sympathy with the restoration of the monarchy in Hungary. The Egyptian press concentrated on the attempts of Charles IV, to regain his Hungarian throne. They were indicated as positive events which can be connected with the fact that the Egyptian public was committed to the monarchy. The Hungarian Prime Minister, Gyula Gömbös’s orientation to Rome and Berlin in 1930 was highlighted. Duel between Gyula Gömbös and Tibor Eckhardt reflected as an act of European gallantly which resolves disputes. The news of the duel evoked sympathy in archaic groups of Egyptian society suggesting that the principle of tit for tat law prevailed in Hungary. In 1936 the Italian visit of the Prime Minister, Gyula Gömbös and Foreign Minister, Kálmán Kánya and the Italian-Hungarian-Austrian Treaty were of primary interest of London, as the treaty was against Germany’s claim to annex Austria (Anschluss), and laid the foundation for the establishment of a customs union among the three states, which prevented the German economic penetration into Central Europe. Accordingly, it can be concluded that the Egyptian press positively portrays the newly reformed independent Hungary, especially the consolidation of István Bethlen in the 1920s, and the most important governmental, economical, commercial, and military events in the 1930s.